2014
DOI: 10.1007/s00244-014-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China

Abstract: Perchlorate is used widely in fireworks, and, if ingested, it has the potential to disrupt thyroid function. The concentrations of perchlorate in water and soil samples and in urine samples of women of reproductive age from Liuyang, the largest fireworks production area in China, were investigated. The results showed that the average perchlorate concentrations in groundwater, surface water, farmland soil, and urine samples of women from the fireworks production area were significantly greater than those from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…Certainly, further studies and affirmations are required to describe the correlation of goitrogen exposure and the size of newborns, as also in this case, existing reports [124][125][126][127] do not allow for the formulation of unambiguous conclusions. In addition to the studies presented in the present review, perchlorate in human urine have also been found in China [8,140], in Haiti [141] and Kuwait [142] and in maternal milk in the USA [83,143] and in human blood in China [144]. The increasing number of current perchlorate studies in various countries indicates that the perchlorate problem is still not fully understood and assessed.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 55%
See 1 more Smart Citation
“…Certainly, further studies and affirmations are required to describe the correlation of goitrogen exposure and the size of newborns, as also in this case, existing reports [124][125][126][127] do not allow for the formulation of unambiguous conclusions. In addition to the studies presented in the present review, perchlorate in human urine have also been found in China [8,140], in Haiti [141] and Kuwait [142] and in maternal milk in the USA [83,143] and in human blood in China [144]. The increasing number of current perchlorate studies in various countries indicates that the perchlorate problem is still not fully understood and assessed.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 55%
“…Over the last 10 years, numerous studies also describe other possible perchlorate side effects than just thyroid effects. There are also works on the risk of diabetes, thyroid cancer, changes in blood morphology, parathyroid disorder or even hearing disorders [135][136][137][138][139][140]. The latter are less frequent than those focusing on disruptions of thyroid hormone levels, which are often missed out in various studies.…”
Section: Other Potential Perchlorate Exposure Health Riskmentioning
confidence: 99%
“…Wu et al (2010) reported that tap water perchlorate levels in both of the provinces were significantly higher than those in other investigated locations in China. Furthermore, the urinary perchlorate levels in the general population living in fireworks production area were an order of magnitude higher than those found in populations in other areas in China (Li et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…It is a tradition in China to display fireworks and firecrackers during celebration; in Nanchang city, approximately 376 tons of fireworks trashes were generated in 2012 during the 7-day Chinese New Year celebration. The manufacture and exhibition of fireworks in China are notable sources of perchlorate in the environment (Li et al, 2014;Shi et al, 2011;Wilkin et al, 2007;Wu et al, 2011); and perchlorate-polluted environment can increase the perchlorate exposure levels in Chinese people (Li et al, 2014;Wu et al, 2010). Two thirds of fireworks factories in China are located in Hunan and Jiangxi Provinces (Fig.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, the effects of iodine intake and environmental pollutants such as perchlorate on thyroid tumors and their interactions cannot be ignored, but the evidence for such effects remains scarce. Perchlorate is mainly used for the production of rocket fuel and fireworks as oxidants in explosives [ 9 ]; with its high water solubility, stability, and difficulty to degrade, it is widely present in water, soil, air, and crops [ 10 ]. Most people are exposed to perchlorate through the dietary route [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%